Pengaruh Model Problem Based Learning Terintegrasi Virtual Lab Terhadap Kemampuan Berpikir Kritis Siswa Pada Materi Perubahan Energi - Muawanah, Nidaul (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
The ability to think critically plays a crucial role in the learning process, enabling students to develop cognitive skills and overcome challenges. The expression of critical thinking skills is reflected in the way students solve problems, analyze ideas based on facts, and formulate conclusions. Science education emphasizes the student's ability to build and develop critical, logical, analytical, systematic, empirical, and exploratory thinking to discover ideas and creativity through various activities linked to real-life conditions. This study aims to explain the influence of the Problem-Based Learning (PBL) Model Integrated with Virtual Lab on Students' Critical Thinking Skills in Energy and Its Transformations Material in Grade IV at Muslim Cendekia Elementary School.This research employs a quantitative approach with a quasi-experimental design method, specifically the Nonequivalent Control Group Design. A quasi-experiment is an experimental design conducted without randomization, but still involves dividing participants into groups. Based on Table 4.4, the t-value for critical thinking skills is 4.251 with a probability of 0.000. Since the probability (Sig.) 0.000 ≤ 0.05, H0 is rejected and Ha is accepted, indicating a significant influence of the PBL model integrated with Virtual Lab on students' critical thinking skills. The results demonstrate that the Problem-Based Learning (PBL) model integrated with the PhET Virtual Lab significantly affects critical thinking skills. Each aspect of the model helps students solve problems when using the PBL-Virtual Lab PhET. The integrated PBL with Virtual Lab PhET directly provides students with experiential knowledge and understanding of the subject matter.